Milly, Molly and BB Brown - Pittar, Gill; Morrell, Cris (Milly Molly Books Gisborne, N.Z., 2003)
BB Brown is taken on a visit to the local jail to discourage him from stealing. Includes teaching guide. Suggested level: junior